2018
DOI: 10.1177/0361198118755665
|View full text |Cite
|
Sign up to set email alerts
|

First Application of UHPC Bridge Deck Overlay in North America

Abstract: Deterioration of existing bridge decks, which usually originates with the deck cracking on the top surface, is a common problem in North America. It causes frequent repair of the decks to limit further damage resulting from water/chloride ingress. Superior engineering and durability properties facilitate the use of ultra-high performance concrete (UHPC) as an attractive alternative for a deck overlay, minimizing both deck deterioration and maintenance costs. Recently developed UHPC thixotropic mix designs, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Since its invention, UHPC technology has been evolved over the years and many patents have been developed by companies such as Ductal® of Lafarge and 'Ryerson UHPC' developed by Ryerson research (Acker & Behloul, 2004;Hossain et al, 2012a). UHPC has been successfully used in various types of construction including bridges, seismic-resistant and explosion-resistant structures over the world (Bierwagen & Abu-Hawash, 2018). Study on the bond behaviour of steel and GFRP bars showed superior bond performance of UHPC compared to conventional concrete (Hossain et al, 2017;Logan, 1997;Meda & Rosati, 2003).…”
Section: List Of Symbols and Abbreviationsmentioning
confidence: 99%
“…Since its invention, UHPC technology has been evolved over the years and many patents have been developed by companies such as Ductal® of Lafarge and 'Ryerson UHPC' developed by Ryerson research (Acker & Behloul, 2004;Hossain et al, 2012a). UHPC has been successfully used in various types of construction including bridges, seismic-resistant and explosion-resistant structures over the world (Bierwagen & Abu-Hawash, 2018). Study on the bond behaviour of steel and GFRP bars showed superior bond performance of UHPC compared to conventional concrete (Hossain et al, 2017;Logan, 1997;Meda & Rosati, 2003).…”
Section: List Of Symbols and Abbreviationsmentioning
confidence: 99%
“…Normal-strength concrete (NSC) bridge decks have proved to deteriorate due to various factors, including poor initial quality and both environmental and mechanical distress [1]. Deterioration reduces the load capacity of the bridge and shortens its longevity, thus requiring rehabilitation of the bridge deck or even complete replacement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it also has improved flexural (tensile) strength and ductility due to the addition of high-strength steel fibers to its composition. These improved 1 kg 137 HRWRA 2 L 42.1 Water kg 145 1 Selected mixture comprised steel fibers at volume of 1.75%. 2 High-range water reducing admixture (HRWRA).…”
Section: Introductionmentioning
confidence: 99%
“…The first U.S. deployment of UHPC as a bridge deck overlay was completed on a reinforced concrete slab bridge located on Laporte Road bridge in Mud Creek in May 2016 [21]. The performance of typical UHPC as a filed-cast overlay, (e.g., industrial floors, industrial pavements, and white toppings) embodies several disadvantages, mostly related to the low water/binder ratio, such as workability, finish-ability, and autogenous shrinkage [22][23].…”
Section: Introductionmentioning
confidence: 99%